Summer of the sea serpent - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2004)
Jack and Annie travel in their magic tree house to the land of the mystical selkies to seek a magical sword for Merlin.
"A Stepping Stone book."
Series no. from jacket.
Keywords: Time travel -- Fiction; Magic -- Fiction; Selkies -- Fiction; Swords -- Fiction; Tree houses -- Fiction; Brothers and sisters -- Fiction